2013
DOI: 10.1002/qre.1610
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Analysis and Comparison Between Automatic and Manual Load Haul Dump Machines

Abstract: a Today's trend of replacing manually operated vehicles with automated ones will have an impact not only on machine design, working environment and procedures but also on machine breakdown and maintenance procedures. In the harsh environment of underground mines, the transition from manual to automatic operation is believed to fundamentally change the basis for break downs, maintenance and machine design. In this paper, differences and similarities between manual and automatic underground loading equipment is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Ascher and Feingold [11] observed that reliability engineers treated times between failures as independent and identically distributed and fit probability models, such as Weibull. They advocated the use of nonstationary stochastic point process models, describing a methodology for analysing the data of repairable systems, used in Gustafson et al [12], to compare automatic and manual load haul dump machines from a reliability perspective. Several techniques based on statistical methods [13], artificial intelligence [14], Monte Carlo simulation [15], and non-linear programming [16] have been used to forecast spare part demands.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Ascher and Feingold [11] observed that reliability engineers treated times between failures as independent and identically distributed and fit probability models, such as Weibull. They advocated the use of nonstationary stochastic point process models, describing a methodology for analysing the data of repairable systems, used in Gustafson et al [12], to compare automatic and manual load haul dump machines from a reliability perspective. Several techniques based on statistical methods [13], artificial intelligence [14], Monte Carlo simulation [15], and non-linear programming [16] have been used to forecast spare part demands.…”
Section: Literature Overviewmentioning
confidence: 99%
“…The rules that allow the company the definition of the range and the assignment of the relative score are subjective and generally defined by maintenance managers. According to Gustafson et al, for example, analysing the results, hydraulics and electrics are still the biggest reasons for machine downtime whether the machine is manual or automatic.…”
Section: Risk‐based Prioritisationmentioning
confidence: 99%
“…On average, 4e5 h of production is lost during the blast window per day using current manual operated equipment [3], however, automated equipment can be operated from the surface during this time to boost productivity. (3) Maintenance e Manually operated equipment is subject to operator error, poor visibility and blind spots, leading to collisions with drift walls, excess tire wear and overwork engines [6,7]. Whereas, automated equipment is associated with fewer collisions, increased tire life, optimized driving and reduced consumption of spare parts [8].…”
Section: Introductionmentioning
confidence: 99%